The Dawn of Everything: A New History of Humanity - Bowles, Samuel (Journal of Economic Literature, 2023)
Samuel Bowles of Santa Fe Institute and CORE Econ reviews “The Dawn of Everything: A New History of Humanity” by David Graeber and David Wengrow. The Econlit abstract of this book begins: “Presents an interpretation of human history that revises long-held assumptions about the emergence of social inequality and hierarchy, considering the implications of this counternarrative for accounts of the origins of farming, property, cities, democracy, slavery, and civilization itself.”